2018
DOI: 10.1080/24694193.2018.1520323
|View full text |Cite
|
Sign up to set email alerts
|

The Post-Intensive Care Syndrome in Children

Abstract: Improvements in devices and techniques used to provide life support for patients at intensive care units have reduced patient mortality. Increases in the number of survivors from a critical illness have brought long-term complications experienced during the post-intensive care period into question. The term postintensive care syndrome (PICS) is defined as a new and deteriorating disorder in the cognitive, mental, and physical health status experienced by the survivor after intensive care unit discharge that mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
2
17
0
2
Order By: Relevance
“…At 2-year follow-up, only a few psychosocial domains in mainly older children remained impaired, whereas problems in other psychosocial multiitem domains, i.e., temperament and moods, getting along, and self-esteem, and single utility HUI scores emotions and cognition had normalized as compared with healthy control children. This is in line with a recent review that found that parent-reported HRQoL of children improved over time after critical illness [20]. Apparently, after PICU admission, the physical domain remained most impaired on the longer term.…”
Section: Hrqol Of Critically Ill Children Versus Healthy Control Chilsupporting
confidence: 91%
See 2 more Smart Citations
“…At 2-year follow-up, only a few psychosocial domains in mainly older children remained impaired, whereas problems in other psychosocial multiitem domains, i.e., temperament and moods, getting along, and self-esteem, and single utility HUI scores emotions and cognition had normalized as compared with healthy control children. This is in line with a recent review that found that parent-reported HRQoL of children improved over time after critical illness [20]. Apparently, after PICU admission, the physical domain remained most impaired on the longer term.…”
Section: Hrqol Of Critically Ill Children Versus Healthy Control Chilsupporting
confidence: 91%
“…Two years after PICU stay, children showed most impairments in physical HRQoL domains and therefore, follow-up programs should focus on these physical problems after PICU admission [20]. In addition, psychologists should screen on developmental problems in younger children and mental health problems in schoolaged children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As surviving critical illness can have long-term effects on both PICU survivors and parents, who play a key role in helping to recover, follow-up care for parents is necessary to be able to adequately support the patient and parents. Early mobility exercises, the practice of physical therapy during critical illness, and family engagement/empowerment are promising intervention strategies ( 91 , 92 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is hugely problematic as survival from PIC admission is high (at around 96%) 17 compared with that of adult ICU. In addition, as these are children (most young children <2 years of age) with a whole life ahead of them, a lack of follow up (to identify problems early and instigate support) may lead to life long problems (psychological, social, cognitive, and physical) for both the child and their family 18 . Three years on from this survey, it would be useful to re‐examine this and determine if any progress has been made.…”
mentioning
confidence: 99%